Effect of liquid urea ammonium nitrate application at varying depths on root and shoot growth in wheat (Triticum aestivum) - SUNDARAM, PREM K; MANI, INDRA; KUMAR, ADARSH; LANDE, SATISH D; SARKAR, SUSHEEL K; MANJAIYA, K M; SAHOO, R N; LAL, SANDEEP K (The Indian Journal of Agricultural Sciences, 2017)
An experiment was conducted to optimise the desired concentration of urea ammonium nitrate (UAN), a liquid fertilizer, and its suitable depth of application in wheat (Triticum aestivum L.) during 2016-17 in a completely randomized factorial design. The wheat seed germination was affected both on blotting paper and in soil mixed with different UAN:water dilutions. Viability test showed that when soil was mixed with UAN:water dilution ratio of less than 1:20, all the embryos were destroyed. The cultivar HD 2967 was grown in cylindrical poly vinyl chloride tubes where two different dilution ratio of UAN:water, viz. 1:5 (U1) and 1:10 (U2) were used as fertilizer @ 120N kg/ha. The fertilizer was placed at three depths below the seed, i.e. at 1 (D1), 2 (D2) and 3 cm (D3).The shoot and root growth parameters up to 34 days after sowing were recorded. Both fertilizer concentration and depth of its placement significantly affected plant height, root length, root surface area and root tips at 8, 20 and 34 DAS. At higher concentration of UAN (U1), the root growth significantly reduced by about 43% as that of U2 after 8 DAS. However, after 34 DAS, it was reduced to 16% which shows that the plants were able to overcome the initial shock given by high concentration of UAN. Root surface area was maximum at U2D3 (7.04, 18.26 and 40.89 cm2) and minimum at U1D1 (0.91, 7.46 and 15.24 cm2) after 8, 20 and 34 DAS, respectively. Root tip numbers were also affected at 8 DAS. However, it was non-significantly affected by concentration and depths at 34 DAS. Deep placement of fertilizer at 3 cm showed significantly better growth of both root and shoot in plants. Higher fresh root weight at all the growth stages was observed in D3, which was at par to D2 at 8 DAS. Similarly, highest root and shoot growth were observed at U2D2 which was statistically at par to U1D3. The UAN may be applied in 1:10 dilution ratio at 2 cm depth or 1:5 dilution ratio at 3 cm depth below the seed in order to get better growth of seedlings. Hence, sowing machines for wheat shall be developed keeping in mind these application depths of liquid UAN.